A Novel CD206 Targeting Peptide Inhibits Bleomycin-Induced Pulmonary Fibrosis in Mice - Anghesom Ghebremedhin; Ahmad Bin Salam; Benjamin Adu-Addai; Steve Noonan; Richard Stratton; Md Shakir Uddin Ahmed; Chandra Khantwal; George R. Martin; Huixian Lin; Chris Andrews; Balasubramanyam Karanam; Udo Rudloff; et al. (Cells, 2023)
Activated M2-polarized macrophages are drivers of pulmonary fibrosis in several clinical scenarios, including Idiopathic Pulmonary Fibrosis (IPF). In this study, we investigated the effects of targeting the CD206 receptor in M2-like macrophages with a novel synthetic analogue of a naturally occurring Host Defense Peptide (HDP), RP-832c, to decrease profibrotic cytokines. RP-832c selectively binds to CD206 on M2-polarized bone marrow-derived macrophages (BMDM) in vitro, resulting in a time-dependent decrease in CD206 expression and a transient increase in M1-macrophage marker TNF-α. To elucidate the antifibrotic effects of RP-832c, we used a murine model of bleomycin (BLM)-induced early-stage pulmonary fibrosis. RP-832c significantly reduced fibrosis in a dose-dependent manner, and decreased CD206, TGF-β1, and α-SMA expression in mouse lungs. Similarly, in an established model of lung fibrosis, RP-832c significantly decreased lung fibrosis and significantly decreased inflammatory cytokines TNF-α, IL-6, IL-10, IFN-γ, CXCL1/2, and fibrosis markers TGF-β1 and MMP-13. In comparison with the FDA-approved drugs Nintedanib and Pirfenidone, RP-832c exhibited a similar reduction in fibrosis compared to Pirfenidone, and to a greater extent than Nintedanib, with no apparent toxicities observed. In summary, our findings showed that inhibiting the profibrotic alternatively activated M2-like macrophages using a novel peptide, RP-832c, could reduce BLM-induced pulmonary fibrosis in mice, warranting the therapeutic potential of this peptide for patients with pulmonary fibrosis.